Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Coral larvae have unique transcriptomic responses to pathogenic and probiotic bacteria - Erin M. Borbee; Isabella V. Changsut; Kira Bernabe; Alicia Schickle; David Nelson; Koty H. Sharp; Lauren E. Fuess (Coral Reefs, 2026)
The growing prevalence of coral disease and other stressors threatens coral reefs, and evidence suggests these stressors not only affect adult corals but may also have impacts on early life stages. Yet, our understanding of coral larval physiology, including immunological function, is significantly limited. Here, we leverage the temperate coral experimental system Astrangia poculata to investigate the transcript-level response of A. poculata to exposure to pathogenic and probiotic bacteria. The bacteria tested in the experiment were the known coral pathogen ( Vibrio coralliilyticus RE22) and a probiont ( Phaeobacter inhibens S4) previously demonstrated to inhibit the pathogen’s growth. In this study, we aim to (1) characterize the general immune response of A. poculata larvae to bacterial stimuli, (2) identify defense mechanisms that may aid in host resistance to pathogens, and (3) characterize the impacts of probiont exposure on A. poculata larval gene expression. Our data identify both shared and divergent larval immune responses to probiotic and pathogenic bacteria. Immunological peptidases were enriched in response to bacteria—expression of endopeptidases increased in response to probiont and pathogen, and metallopeptidase activity was enriched in response to the pathogen. Clustering analyses further revealed a diverse array of immune components in response to the pathogen, while its response to the probiont was associated with a broad range of developmental and metabolic terms. Collectively, the data from this study identify immune components that may play a role in coral response to bacteria during their early life stages, with broad relevance to current restoration and conservation approaches.

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

Telehealth Follow-Up for Chronic Migraine Treated With OnabotulinumtoxinA: Patient-Reported Satisfaction - Kelly Harper; Shuang Wu; Sheffield Sharp; Jacqueline Meystedt; Kian Pazira; David Charles (Toxicon, 2026)

Physician Assessment of Non-Medical Toxin Switching on Patient Care - David Charles; Lily Venditti; Mariana Nelson; Ritu Singh; Kian Pazira; Haley Kling; Leeza Kopaeva; Sheffield Sharp; Kelly Harper (Toxicon, 2026)

Patient Perspectives on Nonmedical Toxin Switching and Care - David Charles; Lily Venditti; Mariana Nelson; Ritu Singh; Kian Pazira; Haley Kling; Leeza Kopaeva; Sheffield Sharp; Kelly Harper (Toxicon, 2026)

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Downregulation of Fidgetin-Like 2 Increases Microglial Function: The Relationship Between Microtubules, Morphology, and Activity - Austin N. Smith; Alison Gregor; Lisa Baker; David J. Sharp; Kimberly R. Byrnes (Molecular Neurobiology, 2025)
The microtubule cytoskeleton regulates microglial morphology, motility, and effector functions. The microtubule-severing enzyme, fidgetin-like 2 (FL2), negatively regulates cell motility and nerve regeneration, making it a promising therapeutic target for central nervous system injury. Microglia perform important functions in response to inflammation and injury, but how FL2 affects microglia is unclear. In this study, we investigated the role of FL2 in microglial morphology and injury responses in vitro. We first determined that the pro-inflammatory stimulus, lipopolysaccharide (LPS), induced a dose- and time-dependent reduction in FL2 expression associated with reduced microglial ramification. We then administered nanoparticle-encapuslated FL2 siRNA to knockdown FL2 and assess microglial functions compared to negative control siRNA and vehicle controls. Time-lapse live-cell microscopy showed that FL2 knockdown increased the velocity of microglial motility. After incubation with fluorescently labeled IgG-opsonized beads, FL2 knockdown increased phagocytosis. Microglia were exposed to low-dose LPS after nanoparticle treatment to model injury-induced cytokine secretion. FL2 knockdown enhanced LPS-induced cytokine secretion of IL-1α, IL-1β, and TNFα. These results identify FL2 as a regulator of microglial morphology and suggest that FL2 can be targeted to increase or accelerate microglial injury responses. Graphical Abstract

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Redundancy of p75NTR neurotrophin receptor function in development, growth and fertility in the rat - Stephen Meek; Karamjit Singh-Dolt; Linda Sutherland; Matthew G. F. Sharp; Jorge Del-Pozo; David Walker; Tom Burdon (Transgenic Research, 2024)
The p75NTR neurotrophin receptor has positive and negative roles regulating cell survival in the nervous system. Unambiguous interpretation of p75NTR function in vivo has been complicated, however, by residual expression of alternate forms of p75NTR protein in initial p75NTR knock-out mouse models. As rats are the preferred rodent for studying brain and behaviour, and to simplify interpretation of the knock-out phenotype, we report here the generation of a mutant rat devoid of the p75NTR protein. TALEN-mediated recombination in embryonic stem cells (ESCs) was used to flank exon 2 of p75NTR with Lox P sites and produce transgenic rats carrying either un-recombined floxed p75NTR Ex2-fl , or recombined, exon-2 deleted p75NTR Ex2-Δ alleles. Crossing p75NTR Ex2-fl rats with a Cre -deleter strain efficiently removed exon 2 in vivo. Excision of exon 2 causes a frameshift after p75NTR Gly23 and eliminated p75NTR protein expression. Rats lacking p75NTR were healthy, fertile, and histological analysis did not reveal significant changes in cellular density or overall structure in their brains. p75NTR function is therefore largely dispensable for normal development, growth and basal homeostasis in the rat. However, the availability of constitutive and conditional p75NTR Ex2-Δ rats provides new opportunities to investigate specific roles of p75NTR upon injury and during tissue repair.

Transitional dynamics from mercury to cyanide-based processing in artisanal and small-scale gold mining: Social, economic, geochemical, and environmental considerations - Aaron Malone; Linda Figueroa; Weishi Wang; Nicole M. Smith; James F. Ranville; David C. Vuono; Francisco D. Alejo Zapata; Lino Morales Paredes; Jonathan O. Sharp; Christopher Bellona (Science of The Total Environment, 2023)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Paleoenvironmental and diagenetic evolution of the Aptian Pre-Salt succession in Namibe Basin (Onshore Angola) - Mar Moragas; Vinyet Baqués; Juan Diego Martín-Martín; Ian Sharp; Fabio Lapponi; David Hunt; Michael Zeller; Jaume Vergés; Grégoire Messager; Laurent Gindre-Chanu; Roger Swart; Vladimir Machado (Marine and Petroleum Geology, 2023)

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

DISSOLUTION PROFILE SIMILARITY ANALYSES—STATISTICAL PRINCIPLES, METHODS AND CONSIDERATIONS - Thomas Hoffelder; David Leblond; Leslie Van Alstine; Dorys Argelia Diaz; Sandra Suarez-Sharp; Krista Witkowski; Stan Altan; James Reynolds; Zachary Bergeron; Kevin Lief; Yanbing Zheng; Andreas Abend (The AAPS Journal, 2022)

Current Approaches for Dissolution Similarity Assessment, Requirements, and Global Expectations - Andreas M. Abend; Limin Zhang; Emilija Fredro-Kumbaradzi; Thomas Hoffelder; Michael J. Cohen; Om Anand; Poonam Delvadia; Haritha Mandula; Zhen Zhang; Evangelos Kotzagiorgis; Susan Lum; Victor Gomes Pereira; et al. (The AAPS Journal, 2022)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

In Vitro Dissolution Profiles Similarity Assessment in Support of Drug Product Quality: What, How, When—Workshop Summary Report - Sandra Suarez-Sharp; Andreas Abend; Thomas Hoffelder; David Leblond; Poonam Delvadia; Elisabeth Kovacs; Dorys Argelia Diaz (The AAPS Journal, 2020)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Michael Frei; Kent Burkey; Lisa Emberson; Johan Uddling; Malin Broberg; Zhaozhong Feng; Kazuhiko Kobayashi; Madhoolika Agrawal (Global Change Biology, 2018)
Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic variation in response being most pronounced for soybean and rice. Based on stomatal uptake, we estimate that ozone (mean of 2010–2012) reduces global yield annually by 12.4%, 7.1%, 4.4% and 6.1% for soybean, wheat, rice and maize, respectively (the “ozone yield gaps”), adding up to 227 Tg of lost yield. Our modelling shows that the highest ozone‐induced production losses for soybean are in North and South America whilst for wheat they are in India and China, for rice in parts of India, Bangladesh, China and Indonesia, and for maize in China and the United States. Crucially, we also show that the same areas are often also at risk of high losses from pests and diseases, heat stress and to a lesser extent aridity and nutrient stress. In a solution‐focussed analysis of these results, we provide a crop ideotype with tolerance of multiple stresses (including ozone) and describe how ozone effects could be included in crop breeding programmes. We also discuss altered crop management approaches that could be applied to reduce ozone impacts in the shorter term. Given the severity of ozone effects on staple food crops in areas of the world that are also challenged by other stresses, we recommend increased attention to the benefits that could be gained from addressing the ozone yield gap.

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Update to the Global Climate Data package: analysis of empirical bias correction methods in the context of producing very high resolution climate projections - Thomas M. Mosier; David F. Hill; Kendra V. Sharp (International Journal of Climatology, 2018)
While global climate models (GCMs) are useful for simulating climatic responses to perturbations in the Earth's climate system, there are many instances where higher spatial resolution information is necessary. In all instances, interpretation of interpolated or downscaled GCMs must be done cautiously because each method has its own set of assumptions and potential disadvantages. Here, we present an update to the Global Climate Data (GCD) package, which enables the package to efficiently bias correct and interpolate precipitation and air temperature output from GCM simulations to very high spatial resolutions using the delta change method. While the delta change method is relatively simple, it has previously been shown to enhance the physical representation of interpolated climate time‐series compared to directly interpolating the gridded climate time‐series to a higher spatial resolution. The bias correction methods programmed into the GCD package are univariate empirical quantile mapping (QM) and bivariate empirical joint bias correction (JBC). The skill of QM and JBC for improving GCM simulations processed with the delta change method is evaluated through comparing the cumulative distribution functions (CDFs) of the interpolated GCM simulations to the CDFs of Global Historical Climatology Network (GHCN) station observations for three test regions: Oregon (in the USA), the Alps (spanning several countries in Europe), and the Ganges Delta (in India and Bangladesh). We also assess the representation of precipitation and mean temperature joint probability distributions relative to those present in GHCN station observations. Overall, GCM simulations that are bias corrected with QM prior to being input to the delta change method perform best under our analysis.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Critical Review on the Public Health Impact of Norovirus Contamination in Shellfish and the Environment: A UK Perspective - Francis Hassard; Jasmine H. Sharp; Helen Taft; Lewis LeVay; John P. Harris; James E. McDonald; Karen Tuson; James Wilson; David L. Jones; Shelagh K. Malham (Food and Environmental Virology, 2017)

The carbon fertilization effect over a century of anthropogenic CO 2 emissions: higher intracellular CO 2 and more drought resistance among invasive and native grass species contrasts with increased water use efficiency for woody plants in the US Southwest - Brandon L. Drake; David T. Hanson; Timothy K. Lowrey; Zachary D. Sharp (Global Change Biology, 2017)
From 1890 to 2015, anthropogenic carbon dioxide emissions have increased atmospheric CO 2 concentrations from 270 to 400 mol mol −1 . The effect of increased carbon emissions on plant growth and reproduction has been the subject of study of free‐air CO 2 enrichment ( FACE ) experiments. These experiments have found (i) an increase in internal CO 2 partial pressure ( c i ) alongside acclimation of photosynthetic capacity, (ii) variable decreases in stomatal conductance, and (iii) that increases in yield do not increase commensurate with CO 2 concentrations. Our data set, which includes a 115‐year‐long selection of grasses collected in New Mexico since 1892, is consistent with an increased c i as a response to historical CO 2 increase in the atmosphere, with invasive species showing the largest increase. Comparison with Palmer Drought Sensitivity Index ( PDSI ) for New Mexico indicates a moderate correlation with Δ 13 C ( r 2 = 0.32, P r 2 = 0.00, P = 0.91) after 1950. These results indicate that increased c i may have conferred some drought resistance to these grasses through increased availability of CO 2 in the event of reduced stomatal conductance in response to short‐term water shortage. Comparison with C 3 trees from arid environments ( Pinus longaeva and Pinus edulis in the US Southwest) as well as from wetter environments ( Bromus and Poa grasses in New Mexico) suggests differing responses based on environment; arid environments in New Mexico see increased intrinsic water use efficiency ( WUE ) in response to historic elevated CO 2 while wetter environments see increased c i . This study suggests that (i) the observed increases in c i in FACE experiments are consistent with historical CO 2 increases and (ii) the CO 2 increase influences plant sensitivity to water shortage, through either increased WUE or c i in arid and wet environments, respectively.

Plate-based diversity subset screening generation 2: an improved paradigm for high-throughput screening of large compound files - Andrew S. Bell; Joseph Bradley; Jeremy R. Everett; Jens Loesel; David McLoughlin; James Mills; Marie-Claire Peakman; Robert E. Sharp; Christine Williams; Hongyao Zhu (Molecular Diversity, 2016)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

30‐Arcsecond monthly climate surfaces with global land coverage - Thomas M. Mosier; David F. Hill; Kendra V. Sharp (International Journal of Climatology, 2014)
Monthly total precipitation and mean temperature climate surfaces, gridded to 30‐arcseconds (≈1 km at the equator) and available for all global land areas, are presented. These datasets are generated with a Delta downscaling method, using the 30‐arcsecond WorldClim climatologies to scale monthly anomaly grids. For monthly mean temperature, the anomalies are constructed from both the Climate Research Unit ( CRU ) and Willmott & Matsuura (W&M) 0.5 degree time‐series datasets, whereas for monthly precipitation Global Precipitation Climatology Centre ( GPCC ) data are also used. The 0.5 degree anomalies are then interpolated to the 30‐arcsecond resolution. Use of piecewise cubic Hermite interpolating polynomials (PCHIP) to interpolate the anomaly grids results in more physically representative Delta downscaled surfaces, compared to bilinear and cubic spline interpolation. The Delta downscaled products are compared to Global Historical Climatology Network ( GHCN ) station records for six test regions distributed globally. In this analysis, the Delta grids produced using the W&M time‐series dataset perform better than grids produced using GPCC or CRU . Using Oregon, USA as a test region, the Delta downscaled datasets are compared to the Parameter‐elevation Regressions on Independent Slopes Model ( PRISM ) datasets. For monthly precipitation, PRISM performs better than each of the three Delta downscaled datasets, but for mean temperature both Delta downscaled datasets outperform PRISM . Through computing the Pearson product–moment correlation coefficient between GHCN station delineated errors in the WorldClim climatologies and the Delta downscaled W&M data, it is shown that performance of the Delta grids corresponds strongly to performance of the reference climatologies. Therefore, future improvement of the 30‐arcsecond Delta grids described in this article is strongly tied to advances in the high‐resolution climatological data for all global land surfaces. The Delta downscaled datasets discussed herein are open‐source and freely distributed at http://www.globalclimatedata.org .

Plate-based diversity subset screening: an efficient paradigm for high throughput screening of a large screening file - Andrew S. Bell; Joseph Bradley; Jeremy R. Everett; Michelle Knight; Jens Loesel; John Mathias; David McLoughlin; James Mills; Robert E. Sharp; Christine Williams; Terence P. Wood (Molecular Diversity, 2013)

Aquifer-yield continuum as a guide and typology for science-based groundwater management - Suzanne A. Pierce; John M. Sharp; Joseph H. A. Guillaume; Robert E. Mace; David J. Eaton (Hydrogeology Journal, 2013)

Genetic analysis suggests high conservation value of peripheral populations of Chihuahau chub (Gila nigrescens) - Megan Osborne; Alana Sharp; Jerry Monzingo; David L. Propst; Thomas F. Turner (Conservation Genetics, 2012)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

The Nail as a Noninvasive Indicator of Methylmercury Exposures and Mercury/Selenium Molar Ratios in Brain, Kidney, and Livers of Long-Evans Rats - John Douglas Brockman; Laura Jean Raymond; Carla Rae Ralston; J. David Robertson; Nicole Bodkin; Nicholas Sharp; Nicholas V. C. Ralston (Biological Trace Element Research, 2011)

The molecular basis of anaphase A in animal cells - Uttama Rath; David J. Sharp (Chromosome Research, 2011)

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

Activation of 5-HT6 receptors facilitates attentional set shifting - Katherine E. Burnham; Mark G. Baxter; John R. Bainton; Eric Southam; Lee A. Dawson; David M. Bannerman; Trevor Sharp (Psychopharmacology, 2010)

Television viewing time and weight gain in colorectal cancer survivors: a prospective population-based study - Katrien Wijndaele; Brigid M. Lynch; Neville Owen; David W. Dunstan; Stephen Sharp; Joanne F. Aitken (Cancer Causes & Control, 2009)

Facilitation of extinction of operant behaviour in mice by d-cycloserine - David Shaw; Kelly Norwood; Kim Sharp; Lauren Quigley; Stephen F. J. McGovern; Julian C. Leslie (Psychopharmacology, 2009)

Ages and inferred causes of Late Pleistocene glaciations on Mauna Kea, Hawai'i - Jeffrey S. Pigati; Marek Zreda; Chris Zweck; Peter F. Almasi; David Elmore; Warren D. Sharp (Journal of Quaternary Science, 2008)
Glacial landforms on Mauna Kea, Hawai'i, show that the summit area of the volcano was covered intermittently by ice caps during the Late Pleistocene. Cosmogenic 36 Cl dating of terminal moraines and other glacial landforms indicates that the last two ice caps, called Older Makanaka and Younger Makanaka, retreated from their maximum positions approximately 23 ka and 13 ka, respectively. The margins and equilibrium line altitudes of these ice caps on the remote, tropical Pacific island were nearly identical, which would seem to imply the same mechanism for ice growth. But modelling of glacier mass balance, combined with palaeotemperature proxy data from the subtropical North Pacific, suggests that the causes of the two glacial expansions may have been different. Older Makanaka air atop Mauna Kea was likely wetter than today and cold, whereas Younger Makanaka times were slightly warmer but significantly wetter than the previous glaciation. The modelled increase in precipitation rates atop Mauna Kea during the Late Pleistocene is consistent with that near sea level inferred from pollen data, which suggests that the additional precipitation was due to more frequent and/or intense tropical storms associated with eastward‐moving cold fronts. These conditions were similar to modern La Niña (weak ENSO) conditions, but persisted for millennia rather than years. Increased precipitation rates and the resulting steeper temperature lapse rates created glacial conditions atop Mauna Kea in the absence of sufficient cooling at sea level, suggesting that if similar correlations existed elsewhere in the tropics, the precipitation‐dependent lapse rates could reconcile the apparent difference between glacial‐time cooling of the tropics at low and high altitudes. Copyright © 2008 John Wiley & Sons, Ltd.

Near‐surface‐temperature lapse rates on the Prince of Wales Icefield, Ellesmere Island, Canada: implications for regional downscaling of temperature - Shawn J. Marshall; Martin J. Sharp; David O. Burgess; Faron S. Anslow (International Journal of Climatology, 2007)
Screen temperatures were monitored from May 2001 to April 2003 in an array of 25 sites on the Prince of Wales Icefield, Ellesmere Island, Canada. The observational network covered an area of ca 15 650 km 2 and spanned an altitude ranging from 130 to 2010 m above sea level. The spatial array provides a record of near‐surface‐temperature lapse rates and mesoscale temperature variability on the icefield. The mean daily lapse rate in the 2‐year record is − 4.1° C km −1 , with an average summer lapse rate of − 4.3° C km −1 . Surface‐temperature lapse rates in the region are therefore systematically less than the free‐air lapse rates that are typically adopted for extrapolations of sea‐level temperature to higher altitudes. Steep lapse rates, resembling moist adiabatic rates in the free air (−6 to − 7° C km −1 ), are more common in summer at our site and are associated with enhanced cyclonic activity (low‐pressure and high relative vorticity) and southerly flow aloft. In contrast, northerly, anticyclonic flow prevails when summer lapse rates are weak (above − 2° C km −1 ). The low surface‐temperature lapse rates and their systematic synoptic variability have important implications for applications that require downscaling or extrapolation of surface‐ or boundary‐layer temperatures, such as modelling of glacier mass balance. We illustrate this in an analysis of observed versus modelled snowmelt on the icefield. Copyright © 2006 Royal Meteorological Society.

Fluxes of semivolatile organochlorine compounds in Bow Lake, a high‐altitude, glacier‐fed, subalpine lake in the Canadian Rocky Mountains - Jules M. Blais; David W. Schindler; Martin Sharp; Eric Braekevelt; Melissa Lafreniěre; Karen McDonald; Derek C. G. Muir; William M. J. Strachan (Limnology and Oceanography, 2001)
The fluxes of several organochlorine compounds (OCs) to and from a high‐altitude lake were calculated to determine the relative contributions of rainfall, snowfall, runoff, gas absorption and volatilization, sedimentation, and outflow. Runoff inputs, particularly from a glaciated catchment, and gas absorption were major sources of many OCs. Losses by volatilization, outflow, and sedimentation were also important transport pathways for most OCs. We observed a net deposition of hexachlorocyclohexanes (HCHs) and DDT to Bow Lake by gas exchange, whereas hexachlorobenzene, chlordanes, and most polychlorinated biphenyls were seen to volatilize to the air. The insecticide lindane (γHCH), widely applied across Canada as a seed dressing in early spring, was absorbed by Bow Lake in early summer but gradually equilibrated with water as the summer progressed. This was the result of lower concentrations of γHCH in air and rising air temperatures in late summer. Results indicate that glacially derived tributary inputs are dominant sources of persistent organic pollutants to these glacier‐fed mountain lakes and that smaller contributions may derive from air‐water gas exchange. This study highlights the importance of glacial sources of OCs to mountain lakes and corroborates recent evidence of OC contamination in glacially derived aquatic systems.

Absence of correlation between late-replication and spreading of X inactivation in an X;autosome translocation - Andrew Sharp; David O. Robinson; Patricia Jacobs (Human Genetics, 2001)

Risk Management for Petroleum Reservoir Production: A Simulation-Based Study of Prediction - James Glimm; Shuling Hou; Hongjoong Kim; Yoon-ha Lee; David H. Sharp; Kenny Ye; Qisu Zou (Computational Geosciences, 2001)

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

Age- and tissue-specific variation of X chromosome inactivation ratios in normal women - Andrew Sharp; David Robinson; Patricia Jacobs (Human Genetics, 2000)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Accurate scale up of two phase flow using renormalization and nonuniform coarsening - Timothy C. Wallstrom; Shuling Hou; Michael A. Christie; Louis J. Durlofsky; David H. Sharp (Computational Geosciences, 1999)

Xp deletions associated with autism in three females - N. S. Thomas; Andrew J. Sharp; Caroline E. Browne; David Skuse; Chris Hardie; Nicholas R. Dennis (Human Genetics, 1999)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)